Ada Apa di Balik Mosi Tidak Percaya pada Media Sosial Indonesia? What Lies behind No-Confidence Motion on Indonesian Social Media? - Irfandi Pratama; Zuly Qodir (Society, 2022)
Social media is currently taking on a role as a mobilizing, organizing, and communication tool for social protest movements. Social media platforms facilitate content creation, an emotional and motivational exchange to support and oppose protest activities. Social media can increase protest participation, such as hashtags through Twitter. A negative emotional sentiment triggers the hashtag to become a trending topic in Indonesia. It started with the Environment and Forestry minister’s tweet about development and deforestation, making the public react by raising the hashtag #mositidakpercaya. This study explores the vote of no confidence and the correlation of narrative in the hashtag using a qualitative research method with Q-DAS NVivo 12 Plus analysis. The research data source was obtained from Twitter by capturing the hashtag #mositidakpercaya with supporting data from online media, journal literature, and books. The findings showed that miscommunication and the failure to understand the discussed context were conveyed.